2022
DOI: 10.5812/msnj.123617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Couple Education on Spouses' Anxiety and Treatment Adherence in Patients with Acute Coronary Syndrome Admitted to Cardiac Intensive Care Unit

Abstract: Background: Reducing the anxiety in spouses suffering from cardiovascular diseases is essential for themselves and improving treatment outcomes by increasing adherence to treatment and medication. Objectives: This study aimed to examine the effect of couple education on spouses' anxiety, and treatment adherence in patients with acute coronary syndrome (ACS) admitted to the cardiac intensive care unit. Methods: This quasi-experimental study was conducted on 70 couples, including the spouses and patients with AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Hemmati Maslakpak et al showed that family-based care can increase treatment adherence and reduce fasting blood sugar and glycosylated hemoglobin in diabetic patients (31). Furthermore, Rafeie et al showed that couple training, in addition to reducing the anxiety level of the spouses of patients with acute coronary syndrome, increases treatment adherence in patients (25). Although the research samples and procedures in their study differed from the present study, the patients needed long-term adherence to the treatment regimen due to the chronic nature of both diseases, and the intervention improved their adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemmati Maslakpak et al showed that family-based care can increase treatment adherence and reduce fasting blood sugar and glycosylated hemoglobin in diabetic patients (31). Furthermore, Rafeie et al showed that couple training, in addition to reducing the anxiety level of the spouses of patients with acute coronary syndrome, increases treatment adherence in patients (25). Although the research samples and procedures in their study differed from the present study, the patients needed long-term adherence to the treatment regimen due to the chronic nature of both diseases, and the intervention improved their adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was estimated as 4 persons in each group based on the mean treatment adherence score in a similar study (25) and with a 95% confidence interval and 95% test power using the following formula (26). However, to ensure sample adequacy and account for any probable dropout, the sample size was 40 persons in each group (80 persons total).…”
Section: Methodsmentioning
confidence: 99%